1994
DOI: 10.1007/bf01241804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yogic exercises on thyroid function in subjects resident at sea level upon exposure to high altitude

Abstract: Using radioactive iodine, the effect of 1 month's yogic exercises has been investigated on the thyroid function of subjects resident at sea level (SL) specially after their exposure to high altitude (HA). The results have been compared with a group of SL subjects who underwent physical training (PT) exercises for the same duration. Ten healthy male volunteers in the age range of 20-30 years were used as test subjects in this study with each serving as his own control. The subjects were randomly divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Few studies have investigated the effect of yoga exercises on thyroid function. [47] In a study by Rawal and colleagues, who investigated the effect of one month's yoga and physical training exercise on the thyroid function of subjects, resident at sea level, a greater increase in thyroidal activity was induced by the conventional physical training exercise compared to yoga. [47]…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the effect of yoga exercises on thyroid function. [47] In a study by Rawal and colleagues, who investigated the effect of one month's yoga and physical training exercise on the thyroid function of subjects, resident at sea level, a greater increase in thyroidal activity was induced by the conventional physical training exercise compared to yoga. [47]…”
Section: Discussionmentioning
confidence: 99%
“…The hatha-yoga exercise is considered to improve body functions through the manipulation of cardiovascular, respiratory, metabolic, and other control mechanisms [7]. Ray et al [3] concluded that the practice-selected hatha-yoga exercises can improve muscular endurance and delay the onset of fatigue in middle-aged man.…”
Section: Discussionmentioning
confidence: 99%
“…In control group steady decrease in serum TT 3 , TT 4 and increase in TSH throughout the study suggest their thyroid status from euthyroid to subclinical hypothyroidism indicating polar T 3 syndrome in them as reported by other similar studies 2,6,9 . However in yoga group there is an initial increase in serum TT 3 and TT 4 in May month may be because yoga practice is known to induce hypo-metabolic state thereby decreased peripheral requirement of thyroid hormones 27,31 . Further decrease in weather temperature (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…There are many studies on beneficial effects of yoga [15][16][17][18][19][20][21][22][23][24][25] and it has been reported helpful in imparting cold tolerance also 26 . Yoga induces decreased peripheral demand of thyroid hormones 27 and help in management of hypothyroidism 28,29 but it's efficacy under Antarctic environment is not known. Therefore, it may be hypothesised that yogic intervention for winter members in Antarctica may help mitigating polar T 3 Syndrome.…”
Section: Yoga Interventionmentioning
confidence: 99%